7s + 12 = 131 Therefore, 7s = 119 s = 119/7 Therefore, s = 17
7z + 6s + s = 7z + 7s This can then be factorised using 7 as the factor: 7z + 7s = 7(z + s)
2s2+7s-15 = (2s-3)(s+5) when factored
You said that 4(2s - 1) = 7s + 12Eliminate parentheses: 8s - 4 = 7s + 12Add 4 to each side: 8s = 7s + 16Subtract 7s from each side: s = 16
7s plus 8t plus 10s plus 12t can be simplified to 17s plus 20t.
The equivalent is 7s+2s = 9s
You sure you don't want to add one more s to that? 49s2 + 70s + 25 works out very nicely to (7s + 5)(7s + 5) The one you have doesn't.
8H2S + 8Cl2 -------> S8 + 16HCl. Not happy about that "S8", should it just be "8S"?
8H2S + 8Cl2 ----> S8 + 16HCl
s would be the variable in this equation and after calculating it would be 6/7
13s - 2
7s + 4t